2007
DOI: 10.1093/eurpub/ckl227
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the risk for mental disorders in a representative German adult sample

Abstract: Obesity is associated with a low SES and some somatic disadvantages but not with other social or emotional disadvantages that have been often assumed to be very prevalent in that group. From the population-based perspective, obesity per se seems not to be associated with a higher risk for suffering from mental disorders, whereas relations between specific aspects of obesity and specific types of psychopathology still need further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 38 publications
3
41
2
8
Order By: Relevance
“…We found three additional studies through bibliography hand-searches, yielding 16 relevant publications for this systematic review. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Inter-rater agreement was good for study screening (kappa statistic 0.72, 95% CI: 0.57-0.87) and for quality assessment (kappa 0.75, 95% CI: 0.62-0.88). Tables 1 and 2 summarize the characteristics and main findings of the prospective and cross-sectional studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found three additional studies through bibliography hand-searches, yielding 16 relevant publications for this systematic review. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Inter-rater agreement was good for study screening (kappa statistic 0.72, 95% CI: 0.57-0.87) and for quality assessment (kappa 0.75, 95% CI: 0.62-0.88). Tables 1 and 2 summarize the characteristics and main findings of the prospective and cross-sectional studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies showed a significant positive association [30][31][32]39,[41][42][43] while five showed a positive trend that was nonsignificant for at least one gender stratum. 34,35,37,44,45 In the largest study on obesity and anxiety disorder to date, Zhao et al 45 analyzed data from 177 047 American adults. Participants self-reported any lifetime medically diagnosed anxiety disorder.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations